3D.07: CORRELATION BETWEEN THE ARTERIAL PRESSURE VARIABILITY ESTIMATED AT CLINICS, MAPA AND AMPA. (June 2015) - Abellan-Huerta, J.; García-Escribano, I.A.; Soto, R.M.; Leal, M.; Torres, A.; Guerrero, B.; Melgar, A.C.; Soto, M.; Soria, F.; Abellan-Aleman, J.
Abstract : Objective: To measure the variability (VB) of the arterial pressure (AP) with the use of serial measurements at the clinics (VBCLIN), with 24 h ambulatory monitoring (MAPA) (VBMAPA) and home automonitoring -AMPA- (VBAMPA) and to estimate a relationship among each method. Design and method: This is an observational, descriptive and transversal study assessed with 91 hypertensive patients in treatment and stable with AP < 160/100 mmHg for the last 3 months. Patients between 50–80 years old were included. The VB of the AP was defined as the standard deviation for both, diastolic and systolic pressures. The different VB were determined with the use of tensiometers and validated AP monitors. VBCLIN was estimated from 8 measurements per week in the clinics. A 24 h MAPA was assessed to all the patients included in the study in order to obtain the VBMAPA and an AMPA in two non-consecutive weeks to obtain the VBAMPA (total of 54 measurements). Results: 91 patients with 66 ± 7.7 years old and 58.2% males were recruited. AP values were 134 ± 14/82 ± 10 mmHg for systolic and diastolic APCLIN, respectively. AP values were 122 ± 17 / 68 ± 12 mmHg for systolic and diastolic APMAPA, respectively. AP values were 125 ± 13/75 ± 7 mmHg for systolic and diastolic APAMPA, respectively. The systolic VB for the three above methods was significantly correlated being maximal between VBCLIN and VBAMPA (r = 0.45; 0 < 0.001) and lower for VBCLIN and VBMAPA (r = 0.25; p = 0.015) and VBMAPA and VBAMPA (r = 0.32; p = 0.002). Means of the systolic AP between each method were statistically different except for VBCLIN and VBAMPA. Corresponding to diastolic AP VB, we could only found a significant relationship between VBCLIN and VBAMPA (r = 0.243; p = 0.021). Conclusions: The correlation between VB of AP measured in the clinics, with AMPA and MAPA methods is weak. This observation suggests that these are not interchangeable methodologies. Future studies focused on the relationship between VB —with different methods— and vascular target organ damage would be of great help in order to define the best analytical method.